DIGITALIZATION PROCESSES IN SAMARKAND MUSEUMS DURING THE YEARS OF INDEPENDENCE (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
This thesis examines the digitalization processes in Samarkand museums during the years of independence. The study focuses on the transformation of museum activity from traditional exhibition and storage practices to modern digital forms of preservation, presentation, communication and visitor service. Special attention is paid to the Samarkand State Museum-Reserve and other museums connected with the cultural heritage of the region. The research shows that digitalization in Samarkand museums developed gradually: first through the improvement of documentation and museum registration, then through the modernization of exhibition practice, and later through virtual visits, electronic information resources, online communication and multimedia tools. The thesis concludes that digitalization has become an important factor in preserving cultural heritage, expanding public access to museum collections and strengthening the role of museums in education, tourism and cultural diplomacy.
Keywords: Samarkand museums, digitalization, independence, cultural heritage, virtual visit, museum activity, museum collections, innovation, tourism, historical memory.